Role of Bhabinkamtibmas in Preventing Criminal Acts of Domestic Violence in The Legal Area of The Polres of Kolaka: Peran Bhabinkamtibmas Dalam Mencegah Terjadinya Tindak Pidana KDRT Di Wilayah Hukum Polres Kolaka - Satrio, M Isfan Fajar (Police Studies Review, 2021)
This research is based on the because of the criminal act of domestic violence in the jurisdiction of the Kolaka Police. which resulted in several fatalities caused by the violence, especially wives and children as well as further impacts such as divorce. This study aims to determine the role of Bhabinkamtibmas in preventing the occurrence of domestic violence and the factors that affect Bhabinkamtibmas Kolaka Police and the steps of Bhabinkamtibmas in improving its performance capabilities. The concept of Bhabinkamtibmas, the concept of Polmas and the concept of the prohibition of domestic violence are used, while the implementation uses the Theory of Competence and Management. Research Methods Using a qualitative approach whose results are strengthened by the findings, observations, document studies, with the results of interviews with sources of information. Data analysis techniques include data reduction and formulating working hypotheses by formulating a proportional question. The result of this research is the role of Bhabinkamtibmas Polres Kolaka in Preventing Domestic Violence which refers to Perkap No. 3 of 2015 in terms of community development has been going well. In terms of Early Detection, it has not gone well, and in terms of Mediation/Negotiations it has gone well, meaning that people who complain about domestic violence problems can be resolved through mediation/negotiation rather than through legal channels. Internal and external factors as well as Bhabinkamtibmas' steps in improving abilities, namely increasing knowledge, skills and behavior.